2020
DOI: 10.1016/j.fct.2020.111459
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 2-MCPD on oxidative stress in different organs of male mice

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…Strikingly, these studies identified a previously unreported induction of oxidative stress in the brain. 14,15 Importantly, the effects of 2-MCPD, which has not been studied in carcinogenicity studies, were less pronounced, suggesting that the molecular toxicity mechanisms of 2-MCPD and 3-MCPD are potentially different. 14,15 A similar approach was used to demonstrate the capacity of the food preservative ethoxyquin to induce liver toxicity, using a combination of our hGSTP1 and NRF2-nulled reporter mice.…”
Section: Resultsmentioning
confidence: 99%
“…Strikingly, these studies identified a previously unreported induction of oxidative stress in the brain. 14,15 Importantly, the effects of 2-MCPD, which has not been studied in carcinogenicity studies, were less pronounced, suggesting that the molecular toxicity mechanisms of 2-MCPD and 3-MCPD are potentially different. 14,15 A similar approach was used to demonstrate the capacity of the food preservative ethoxyquin to induce liver toxicity, using a combination of our hGSTP1 and NRF2-nulled reporter mice.…”
Section: Resultsmentioning
confidence: 99%